2000
DOI: 10.1097/00000539-200005000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Fentanyl Is Superior to Intravenous Ondansetron for the Prevention of Perioperative Nausea During Cesarean Delivery with Spinal Anesthesia

Abstract: This study compares intrathecal (IT) fentanyl with IV ondansetron for preventing intraoperative nausea and vomiting during cesarean deliveries performed with spinal anesthesia. Thirty healthy parturients presenting for elective cesarean delivery with standardized bupivacaine spinal anesthesia were randomized to receive 20 microg IT fentanyl (Group F) or 4 mg IV ondansetron (Group O) by using double-blinded methodology. At eight specific intervals during the surgery, a blinded observer questioned the patient ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
57
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 8 publications
10
57
0
3
Order By: Relevance
“…The results are similar to the findings of Singh et al, found pruritus (10%) and Khanna et al has found pruritus in 20% of patients with 25 µg fentanyl. 22,31 Nausea, vomiting was not observed in this study and supported by similar studies by Singh et al and Manullang et al 22,32 The postoperative analgesia was also significantly higher (p =0.000) in Group BF (266.37±9.47 minutes) than in Group B (162.97±9.26 minutes) and the results were correlated with finding of Korhonen et al and Khanna et al 1,31 In this study 14 patients (47%) in group B and 6 (20%) patients in group BF were fast tracked in general ward. Sixteen patients (53%) and 24 (80%) patients in group B and group BF respectively needed to be shifted to PACU and they remained there for 15.69±3.85 and 30.13±10.79 minutes respectively.…”
supporting
confidence: 86%
“…The results are similar to the findings of Singh et al, found pruritus (10%) and Khanna et al has found pruritus in 20% of patients with 25 µg fentanyl. 22,31 Nausea, vomiting was not observed in this study and supported by similar studies by Singh et al and Manullang et al 22,32 The postoperative analgesia was also significantly higher (p =0.000) in Group BF (266.37±9.47 minutes) than in Group B (162.97±9.26 minutes) and the results were correlated with finding of Korhonen et al and Khanna et al 1,31 In this study 14 patients (47%) in group B and 6 (20%) patients in group BF were fast tracked in general ward. Sixteen patients (53%) and 24 (80%) patients in group B and group BF respectively needed to be shifted to PACU and they remained there for 15.69±3.85 and 30.13±10.79 minutes respectively.…”
supporting
confidence: 86%
“…Retching was defined as the labored, spasmodic, and rhythmic contraction of the respiratory muscles without the expulsion of gastric contents. Vomiting was defined as the forceful expulsion of gastric contents from mouth [6].…”
Section: Methodsmentioning
confidence: 99%
“…The Journal of Obstetrics and Gynecology of India (July-August 2012) 62(4):419-423 Randomized, Placebo Controlled Trial of Granisetron techniques [5], peritoneal traction, and exteriorization of uterus [6]. Maternal hypotension after induction of spinal anesthesia may trigger the vomiting center to induce emesis due to hypoxia [7].…”
mentioning
confidence: 99%
“…A randomized double-blinded study of women undergoing elective Cesarean delivery under spinal anesthesia found that intrathecal fentanyl was superior for the prevention of intraoperative nausea when compared with intravenous ondansetron given at the time of spinal placement. 5 In this study, spinal opioids actually reduced nausea during Cesarean delivery, perhaps related to better quality of analgesia. It would be a shame if all these benefits for the mother in labour came with a negative impact on the fetus or newborn.…”
mentioning
confidence: 52%
“…Une étude randomisée à double insu chez des femmes subissant une césarienne programmée sous rachianesthésie a montré que le fentanyl intrathécal était supérieur pour la prévention des nausées peropératoires lorsque comparé à l'ondansétron intraveineux administré au moment du placement du cathéter de rachianesthésie. 5 Au cours de cette étude, les opioïdes rachidiens ont effectivement diminué les nausées au cours de la césarienne, peut-être en rapport avec une meilleure qualité de l'analgésie. 6 En utilisant trois différentes méthodes d'évaluation des nouveau-nés, les auteurs ont réduit la probabilité de passer à côté d'un effet indésirable.…”
unclassified